Measuring dimensionality of cell‐scaffold contacts of primary human bone marrow stromal cells cultured on electrospun fiber scaffolds. Issue 1 (4th October 2022) - Florczyk, Stephanie J.; Hotaling, Nathan A.; Simon, Mylene; Chalfoun, Joe; Horenberg, Allison L.; Schaub, Nicholas J.; Wang, Dongbo; Szczypiński, Piotr M.; DeFelice, Veronica L.; Bajcsy, Peter; Simon, Carl G.
Abstract: The properties and structure of the cellular microenvironment can influence cell behavior. Sites of cell adhesion to the extracellular matrix (ECM) initiate intracellular signaling that directs cell functions such as proliferation, differentiation, and apoptosis. Electrospun fibers mimic the fibrous nature of native ECM proteins and cell culture in fibers affects cell shape and dimensionality, which can drive specific functions, such as the osteogenic differentiation of primary human bone marrow stromal cells (hBMSCs), by. In order to probe how scaffolds affect cell shape and behavior, cell‐fiber contacts were imaged to assess their shape and dimensionality through a novel approach. Fluorescent polymeric fiber scaffolds were made so that they could be imaged by confocal fluorescence microscopy. Fluorescent polymer films were made as a planar control. hBSMCs were cultured on the fluorescent substrates and the cells and substrates were imaged. Two different image analysis approaches, one having geometrical assumptions and the other having statistical assumptions, were used to analyze the 3D structure of cell‐scaffold contacts. The cells cultured in scaffolds contacted the fibers in multiple planes over the surface of the cell, while the cells cultured on films had contacts confined to the bottom surface of the cell. Shape metric analysis indicated that cell‐fiber contacts had greater dimensionality and greater 3D character than the cell‐film contacts. These results suggest that cell adhesion site‐initiated signaling could emanate from multiple planes over the cell surface during culture in fibers, as opposed to emanating only from the cell's basal surface during culture on planar surfaces. Abstract :